2022
DOI: 10.3390/ijerph19094940
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Quality, Insomnia, Anxiety, Fatigue, Stress, Memory and Active Coping during the COVID-19 Pandemic

Abstract: Background: The current study aimed to evaluate the impact of the coronavirus (COVID-19) pandemic on sleep quality, insomnia, anxiety, stress, fatigue and active coping in the United States. Methods: This was a cross-sectional study using a publicly available database taken from the Boston College COVID-19 Sleep and Well-Being Dataset. We have selected the most recent data that included information about sleep quality and other measures, including insomnia, anxiety, stress, fatigue and coping, collected betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
18
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 47 publications
3
18
1
Order By: Relevance
“…51 The mean global PSQI and ISI scores in the current study were within the range observed in England, Italy, the West Balkan, and the USA during the third wave of the COVID-19 pandemic (ISI= 6.9-8.1; PSQI = 5.77-7.62). [52][53][54][55] In the present study, several childhood stressors were found to be associated with a reduction in sleep quality and with increased symptoms of insomnia. The most consistent predictor was the number of ACEs.…”
Section: Discussionsupporting
confidence: 51%
“…51 The mean global PSQI and ISI scores in the current study were within the range observed in England, Italy, the West Balkan, and the USA during the third wave of the COVID-19 pandemic (ISI= 6.9-8.1; PSQI = 5.77-7.62). [52][53][54][55] In the present study, several childhood stressors were found to be associated with a reduction in sleep quality and with increased symptoms of insomnia. The most consistent predictor was the number of ACEs.…”
Section: Discussionsupporting
confidence: 51%
“…The COVID-19 epidemic has impacted the mental health of a wide range of people, including the general public, healthcare professionals, and university students. All studies agree that the epidemic has increased people's stress levels, increasing their risk of developing anxiety, depression, and other mental illnesses [19][20][21][22][23][24][25][26][27]. This study was a cross-sectional web-based survey in Saudi Arabia and Jordan.…”
Section: Discussionmentioning
confidence: 99%
“…In several areas, fatigue remains an important issue that affects individuals' health-related quality of life, employee health, safety, and overall work productivity by 54% [3,4]. Recently, it has become a major concern for the physical and mental health of individuals working under challenging workload conditions during the COVID-19 pandemic [2,[5][6][7]. The prevalence of fatigue among patients who recovered from COVID-19 ranges from 52 to 70% [8,9].…”
mentioning
confidence: 99%